EFEKTIVITAS MEDIA KOMIK DIGITAL TERHADAP KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR - Sutomo; Rida Fironika Kusumadewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of educational technology requires innovative learning media that can enhance students’ learning independence, particularly in elementary mathematics learning. This study aims to analyze the effectiveness of digital comic media in improving learning independence among fifth-grade students at SD Islam Sultan Agung 4 Semarang. A quantitative experimental method with a One Group Pretest–Posttest Design was employed. The research subjects consisted of all fifth-grade students. Data were collected using a learning independence questionnaire administered before and after the implementation of digital comic media. Data analysis involved descriptive statistics and N-Gain analysis to determine the effectiveness of the media. The results showed an improvement in students’ learning independence after the use of digital comic media, indicated by higher posttest scores compared to pretest scores. The average N-Gain score was 0.485, categorized as moderate, indicating that digital comic media is sufficiently effective in enhancing students’ learning independence. Digital comics present learning materials through visual and narrative elements that support students in managing their learning processes more independently. Therefore, digital comic media can be considered an effective alternative learning medium for improving learning independence in elementary schools.